Optimisation of treatment of cancer based on principles of pharmacokinetics - Lee, Jong Bong (2018)
The main hypothesis of this research project was that optimisation of treatment based on pharmacokinetic principles is on its own a powerful approach in improvement of treatment outcomes. This work therefore focused on optimisation of treatment of cancer based on principles of pharmacokinetics using two main approaches 1) lipophilic prodrug approach to specifically target the intestinal lymphatic system following oral administration and 2) identification of orally bioavailable candidate anticancer agents and biopharmaceutical development to increase the bioavailability for sufficient systemic exposure to the drug. The first approach was the prodrug derivatisation to take advantage of the physiological process of intestinal lymphatic transport in order to deliver anticancer agents to the mesenteric lymph nodes. Similar prodrug approaches have been researched by other groups but the main focus previously was on increasing the overall bioavailability where they mostly used long-chain or triglyceride mimetic prodrug moieties. However, in this project, through a series of stability and chylomicron association studies, it was revealed that activated ester prodrugs are the most suitable forms for yielding high concentrations of active drugs in the mesenteric lymph nodes. It was remarkable that using this novel approach significantly higher concentrations of the active drugs were achievable in the intestinal lymphatics without affecting the systemic exposure. The second approach taken in this PhD project was achieving sufficient systemic exposure of anticancer agents by identification of orally bioavailable candidate and improvement of oral bioavailability by biopharmaceutical development. The candidates with promising pharmacokinetic properties were rank-ordered by application of a rational drug discovery and development approach of integrated in vitro-in silico assessments. Following in vivo confirmation studies, oral bioavailability was further enhanced for a compound that exhibited a double-peak phenomenon. The results of the two approaches indicate that pharmacokinetic optimisation can be useful in development of anticancer agents to improve the treatment outcomes of cancer.